2017
DOI: 10.1160/th16-07-0498
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of vitamin K antagonist resumption after upper gastrointestinal bleeding

Abstract: The optimal timing of vitamin K antagonists (VKAs) resumption after an upper gastrointestinal (GI) bleeding, in patients with continued indication for oral anticoagulation, is uncertain. We included consecutive cases of VKA-associated upper GI bleeding from three hospitals retrospectively. Data on the bleeding location, timing of VKA resumption, recurrent GI bleeding and thromboembolic events were collected. A model was constructed to evaluate the 'total risk', based on the sum of the cumulative rates of recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…We evaluated the incidences of different gastrointestinal bleeding levels in six studies. [25][26][27][28]33,34 We found a pooled odds ratio of 2.4…”
Section: Gastrointestinal Bleedingmentioning
confidence: 64%
See 1 more Smart Citation
“…We evaluated the incidences of different gastrointestinal bleeding levels in six studies. [25][26][27][28]33,34 We found a pooled odds ratio of 2.4…”
Section: Gastrointestinal Bleedingmentioning
confidence: 64%
“…However, since the publication of these reviews, several high-quality cohort studies have been published. 27,28,33,34 As a result, an updated knowledge synthesis in terms of a systematic review and meta-analysis is strongly warranted. Therefore, with this systematic review and meta-analysis, we want to compare the evidence on the effects of continuation and discontinuation of anticoagulant/antithrombotic drugs after gastrointestinal bleeding on the overall incidences of gastrointestinal bleeding, thromboembolic events and mortality events.…”
Section: Introductionmentioning
confidence: 99%
“…weeks [27]. Currently, our meta-analysis does not provide evidence to specifically support a time frame for restarting OAC, and any decision making on restarting OAC needs to balance the risks of adverse outcomes.…”
Section: Accepted Manuscript 17mentioning
confidence: 97%
“…Other two studies by the same group tried to investigate in two heterogeneous cohorts, the optimal timing of OAC resumption after ICH and GIB [26,27]. In the first paper, enrolling 234 patients with an ICH (58% with AF as indication for OAC), the authors found out that the combined risk of a recurrent ICH and an ischemic event reached a nadir when OAC was restarted between 10 and 30 weeks [26]; in the second paper, a risk modelling analysis based on 207 patients (63%) with a GIB event, found that the nadir between the recurrent bleeding and thromboembolic occurrence risk was reached restarting the OAC between 3 and 6…”
Section: Accepted Manuscript 17mentioning
confidence: 99%
“…In a multicenter, retrospective study of 207 cases with warfarinassociated upper gastrointestinal bleeding, 121 patients resumed anticoagulation. 52 For equal disutility of gastrointestinal bleeding and stroke, the optimal timing would be between 3 and 6 weeks after the index event. For a disutility 2.1 to 3.1 times higher for stroke than for gastrointestinal bleeding, as concluded from a systematic review of values and preferences, 53 the optimal timing could be between 1 and 3 weeks, but earlier resumption will result in more recurrences of gastrointestinal bleeding with renewed interruption of anticoagulation.…”
Section: Gastrointestinal Hemorrhagementioning
confidence: 99%